Employment Vulnerability And Financial Well-Being In Indonesia: Insights From A Systematic Literature Review - Tarada Berlian Megananda; Dara Sagita Triski (International Journal of Management and Business Economics, 2026)
Employment vulnerability has emerged as a critical issue affecting workers’ financial well-being, particularly in developing economies such as Indonesia, where informal and precarious employment remains widespread. This study aims to systematically review and synthesize existing empirical evidence on the relationship between employment vulnerability and financial well-being among workers in Indonesia. Adopting a Systematic Literature Review (SLR) approach guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, relevant peer-reviewed journal articles were identified, screened, and analyzed thematically. The review focuses on key dimensions of employment vulnerability, including job insecurity, income instability, lack of social protection, and exposure to economic shocks, particularly during the COVID-19 pandemic. The findings reveal that employment vulnerability consistently undermines workers’ financial well-being through increased financial stress, reduced savings capacity, and heightened psychological distress. Moreover, financial literacy and access to financial services emerge as important mitigating factors that can enhance financial resilience among vulnerable workers. The review also highlights significant disparities between formal and informal workers, as well as gaps in policy protection for marginalized groups. This study contributes to the literature by integrating insights from labor economics and financial well-being research, offering policy-relevant implications for improving employment security, financial capability, and social protection systems in Indonesia.